"Mother's Health and Well-Being Matters: Is a Mediated Social Cohesion Public Health Intervention Feasible?". Issue 3 (March 2022) - Jones, Cheryl; Gibbons, Marley; Magsamen-Conrad, Kate; Ulanday, Kathleen T.; Watterson, Jessica; Oakley-Girvan, Ingrid; Houghton, Lauren C.; Gokal, Kajal
Purpose: To test the feasibility of introducing 'Free Time for Wellness' (FT4W) an intervention to increase healthy behaviours and reduce the risk of cancer. Design: Feasibility study; Setting: Washington Heights, New York, USA is a low socioeconomic status area. Subjects: Mothers aged 18 and above with children under 12 years of age and living in Washington Heights were recruited. Intervention: FT4W, a community-based intervention delivered through a neighbourhood-based app, offering weekly dance and yoga classes, food pantry visits and group playdates. Childcare professionals cared for participants' children during wellness activities. Measures: A bespoke before and after survey was designed and tested for its ability to collect relevant data to assess the impact of FT4W. Outcomes included recruitment rates, participation, attrition, acceptability, and success of the community champion. Analysis: Comparisons of proportions and means Results: Twenty-one mothers participated in the study of which 90% attended ≥ 1 FT4W activity; 65% ≥ 2; 52% ≥ 3. The survey was completed by a 100% of participants indicating it was easy to understand and not too burdensome. All measures detected change in constructs from baseline to follow-up. Availability of childcare was the most commonly (66%) reported reason participants were able to engage in the offered wellness activities. Conclusion: Conducting a larger-scale trial to assess the impact of FT4W is feasible considering 4 major lessons. (1) Recruitment, retention, and acceptability rates were high; however, moms need additional support to increase participation in wellness activities and improve tech literacy. (2) Research measures were sensitive enough to detect change, but the timing of assessments needs to be considered. (3) Participants greatly valued access to professional childcare. (4) The Community Champion is a necessary, but difficult role to fill that requires careful consideration by the Institutional Review Board (IRB).